Social Inequality and Inequal Access to Jobs: (A Case Study of Street Buskers and Clowns in Hulu Sungai Utara Regency) - Erfan Maulana; Akhmad Berkatillah (Jurnal Ilmiah Publika, 2025)
The phenomenon of street workers such as buskers and clowns in Hulu Sungai Utara Regency reflects social inequality and limited access to employment that still persists in Indonesia, particularly in regions with uneven economic development. This group is often marginalized from access to education, skills training, and formal employment. This study aims to analyze the factors that drive individuals to work in the informal sector and to identify the role of the government and social organizations in their empowerment. The research applies a descriptive qualitative approach with a case study method, using document analysis from the Central Bureau of Statistics, the Department of Social Affairs, the Department of Manpower, and publications from NGOs working on labor issues. The findings indicate that low education levels, limited skills, lack of employment information, and minimal social protection are the main causes. In addition, negative social stigma and the suboptimal implementation of government policies worsen their condition. The creative economy is seen as an alternative for empowerment through culturally based training and facilitated market access. Therefore, this study recommends cross-sector collaboration to design sustainable and inclusive empowerment programs for street workers